ENTREPRENEURIAL RESILIENCE: CASE STUDIES OF FAILED AND SUCCESSFUL STARTUPS - Nuraiman Nuraiman; Rafiullah Amin; Safiullah Aziz (Journal of Social Entrepreneurship and Creative Technology, 2025)
Entrepreneurial resilience plays a critical role in determining the success or failure of startups, especially in highly volatile and competitive environments. While many studies have focused on the factors leading to startup success, less attention has been paid to how entrepreneurs recover from failure and the key traits that contribute to their resilience. Understanding these dynamics is essential for aspiring entrepreneurs and stakeholders in the startup ecosystem. This research aims to explore the concept of entrepreneurial resilience by analyzing case studies of both failed and successful startups. The study seeks to identify the factors that contribute to entrepreneurial resilience and how these factors influence the ability to recover from failure or sustain success. A qualitative case study approach was employed, focusing on 10 startup companies—5 that failed and 5 that succeeded. Data were collected through in-depth interviews with founders and key stakeholders, as well as secondary sources such as company reports and news articles. Thematic analysis was used to identify recurring patterns and key themes. The study found that successful entrepreneurs exhibited high levels of emotional intelligence, adaptability, and a strong support network. In contrast, failed startups often struggled with a lack of strategic foresight, poor decision-making, and inadequate resource management. Resilience factors, including mindset, leadership, and external support, were crucial in navigating both failure and success.